2010
DOI: 10.1063/1.3406202
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Li+ dipoles at very low concentration in quantum paraelectric potassium tantalate

Abstract: The dynamics of Li+ dipoles distributed in the quantum paraelectric matrix of potassium tantalate is investigated via linear and nonlinear dielectric response. It is found that the highly diluted solid solution K0.995Li0.005TaO3, KLT(005), reveals nearly ideal Debye-type dipolar relaxation with conventional frequency dispersion at intermediate temperatures, 30<T<60 K. At lower temperatures a drastic increase in the linear dielectric susceptibility is measured as predicted by computer simulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Recently Tyunina et al [6] have reported strain-induced ferroelectric order in epitaxial thin film KTaO 3 . Doping KTaO 3 with Li þ ions, K 1À x Li x TaO 3 , causes a very complex polar behavior [1,[7][8][9][10][11][12][13][14][15][16][17][18]. In the case of x 4x cr % 0:02, [8,11], a ferroelectric state appears.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently Tyunina et al [6] have reported strain-induced ferroelectric order in epitaxial thin film KTaO 3 . Doping KTaO 3 with Li þ ions, K 1À x Li x TaO 3 , causes a very complex polar behavior [1,[7][8][9][10][11][12][13][14][15][16][17][18]. In the case of x 4x cr % 0:02, [8,11], a ferroelectric state appears.…”
Section: Introductionmentioning
confidence: 95%
“…At x ox cr a relaxor or glass-like behavior is realized. A large interest is attracted by a very dilute system with a low concentration x o0:01 [15,16]. Because of the high polarizability of the KTaO 3 host lattice with the soft TO 1 transverse optic mode, polar impurities and defects, can strongly influence on physical properties and formation of the polar nanodomains is possible.…”
Section: Introductionmentioning
confidence: 99%
“…That is why the instrument provides high quality nonlinear susceptibility data and in particular appears as a very convenient tool for discrimination between continuous and discontinuous phase transitions when determining the sign of the real part of the third order dielectric susceptibility. We have applied this new instrument to various basic ferroelectric scenarios, such as the classic first-and second-order ferroelectric transitions of barium titanate (BaTiO 3 ) , triglycine sulphate (TGS) and lead germanate (Pb 5 Ge 3 O 11 ) , the double anomalous second-order transitions of Rochelle salt (Miga et al, 2010a), the smeared transition of the classic relaxor ferroelectrics lead magno-niobate (PbMg 1/3 Nb 2/3 O 3 , PMN) and strontium-barium niobate (Sr 0.61 Ba 0.39 Nb 2 O 6, SBN61) , the dipolar glassy and ferroelectric transitions of Li + -doped potassium tantalate (K 1-x Li x TaO 3 , KLT) with x = 0.005, 0.011 and 0.063 (Dec et al, 2010;Miga et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a distribution of relaxation times which increases upon cooling has been recognized before 2,29,30 . It is a reflection of the random distribution of the dipoles and of the varying rates at which different PNDs grow upon cooling.…”
Section: B Dielectric Permittivitymentioning
confidence: 99%